Carpal derangement and associated carpal valgus in a dog - Comerford, E. J.; Doran, I. C.; Owen, M. R. (Veterinary and Comparative Orthopaedics and Traumatology, 2006)
This case report describes derangement of the numbered carpal bones resulting in a valgal growth deformity in the right carpus of a seven-month-old dog. Radiographic assessment of the right carpus revealed abnormalities in the size and shape of the numbered carpal bones and carpal valgus. Surgical correction of the growth deformity was planned by partial carpal arthrodesis; however medial collateral laxity associated with the carpal valgus necessitated a pancarpal arthrodesis to achieve correct limb alignment.
Keywords: Carpus; derangement; valgus deformity; arthrodesis